CAR RENTAL INFORMATION SYSTEM DESIGN AT CV. NUSA RENTCAR BEKASI BASED WEBSITE USING THE WATERFALL METHOD - Setiawan, Riski; Ariani, Fattya; Susanti, Melan; Fahmi, Muhammad; Lubis, Baginda Oloan (Sekolah Tinggi Manajemen Informatika dan Komputer Jayakarta, 2023)
Processing data manually is felt to be very problematic, including when recording cars that are usually rented out, customer records, recording car loan and return transactions, up to reporting car loan and return transactions. Besides that, the marketing and publication activities carried out by the car rental business CV. Nusa Rentcar Bekasi to the wider community still uses pamphlets and advertisements in print media, the impact of the marketing area obtained is very limited so that CV. Nusa Rentcar Bekasi is less known by the wider community. Based on the explanation above, in order to be able to increase and expand market share, make it easy for the general public to obtain information about the services provided by CV. Nusa Rentcar Bekasi and provide convenience to the service sales department in carrying out data processing, data search to report generation, a media or website-based information system is needed that can overcome the problems faced by CV car rental. Nusa Rentcar Bekasi. In this study the system development model used is the Waterfall model. The results of this study can provide several advantages, namely information processing and data management of sales of car rental services at CV. Nusa Rentcar Bekasi is more efficient and effective.